PEMBUATAN ALAT PENGADUK PAKAN TERNAK UNTUK MENDUKUNG USAHA TERNAK BAGI MASYARAKAT ASLI PAPUA DI KELURAHAN KAMUNDU KABUPATEN MERAUKE - Rahangmetan, Klemens A.; Awal, Muhammad (Musamus University, 2023)
In general, traditional pig breeders of indigenous Papuans in the Kamundu sub-district, Merauke Regency, make cages very close to the house or in the yard for reasons of security and manpower to transport pig food from the kitchen to the pen. odor and become a breeding ground for disease. For that we need a tool that is capable of flowing pig food from the cooking cauldron to the pen which is located some distance from the house. In this research, the emphasis is on how to make a tool that is capable of flowing pig food from the container to the cage. The goal to be achieved is the availability of a simple and inexpensive device that is able to transport pig fodder directly from the cooking container to the pen which is a safe distance from a health point of view to the house. The research method used is the observation method. This tool consists of a container in the form of a large cylinder with a stirrer that is driven by an electric motor so that the animal feed can be mixed properly, there is also a diverter which is expected to be able to flow the animal feed directly into the cage.